Analisis Algoritma J48 Pada Pengambilan Keputusan Pemberian Pinjaman Kepada Calon Nasabah - Agnes Irene Silitonga; Lukas Ginting; Enjelina Sinaga; Elson Zega; Samuel Sembiring; Yoakim Simamora (Universitas Methodist Indonesia, 2024)
This research aims to analyze the stages of decision making for granting loans to prospective customers using the J48 Algorithm. Using the